Identification of a variant hotspot in MYBPC3 and of a novel CSRP3 autosomal recessive alteration in a cohort of Polish patients with hypertrophic cardiomyopathy - Lipari M.; Wypasek E.; Karpinski M.; Tomkiewicz-Pajak L.; Laino L.; Binni F.; Giannarelli D.; Rubis P.; Petkow-Dimitrow P.; Undas A.; Grammatico P.; Bottillo I. (Polish Archives of Internal Medicine, 2020)
INTRODUCTION Hypertrophic cardiomyopathy (HCM) is a heart disorder caused by autosomal dominant alterations affecting both sarcomeric genes and other nonsarcomeric loci in a minority of cases. However, in some patients, the occurrence of the causal pathogenic variant or variants in homozygosity, compound heterozygosity, or double heterozygosity has also been described. Most of the HCM pathogenic variants are missense and unique, but truncating mutations of the MYBPC3 gene have been reported as founder pathogenic variants in populations from Finland, France, Japan, Iceland, Italy, and the Netherlands. OBJECTIVES This study aimed to assess the genetic background of HCM in a cohort of Polish patients. PATIENTS AND METHODS Twenty–nine Polish patients were analyzed by a next–generation sequencing panel including 404 cardiovascular genes. RESULTS Pathogenic variants were found in 41% of the patients, with ultra–rare MYBPC3 c.2541C>G (p.Tyr847Ter) mutation standing for a variant hotspot and correlating with a lower age at HCM diagnosis. Among the nonsarcomeric genes, the CSRP3 mutation was found in a single case carrying the novel c.364C>T (p.Arg122Ter) variant in homozygosity. With this finding, the total number of known HCM cases with human CSRP3 knockout cases has reached 3.